How do you simplify -10^2?

2 Answers
Feb 16, 2017

-10^2 = -100
it's helpful for the rest of your math life to view expressions in parentheses

Explanation:

note that -10^2 and (-10)^2 give different results
-10^2 = (-1)(10)(10) = -100
(-10)^2 = (-10)(-10) = 100

think of -10^2 as (-1)(10^2)
and -10^2 is the same as -(10)^2

it's helpful for the rest of your math life to view expressions in parentheses

-10^2 = -100

-100

Explanation:

This question is all about the order of operations: BEMDAS, or

  • B (brackets)
  • E (exponents)
  • M (multiplication)
  • D (division)
  • A (addition)
  • S (subtraction)

The term -10^2 has two operations:

  • multiplication between -1 and 10, and
  • the exponent which takes 10 to the second power

The E, or exponent, comes first:

-10^2=-1xx10^2=-1xx100=-100

If we our question as (-10)^2, then we'd have the B, or term within the bracket go first, which would give us -10, which is then squared to get 100:

(-10)^2=(-1xx10)^2=(-10)(-10)=100